Tax audit in the Polish Deal programme (Discourse of Law and Administration, 2023)
The Polish Deal (Polski Ład) is a government programme effective from the beginningof 2022. It is supposed to help to recover from the economic crisis Poland found itself in after thepandemic. It provides for changes in tax law. In addition to tax changes, it is intended to help solvehousing problems. It also applies to healthcare, retirement and disability pensions, economic activity,social security, and, to a certain extent, labour law. The Polish Deal did not introduce changesto the tax audit, although this had been planned. Tax audit is still regulated primarily by the provisionsof the Tax Ordinance and the Law of Entrepreneurs. It is conducted ex officio and is designedto check the application of tax laws by those being audited. A novelty in the tax legislation is a verificationpurchase, relating to the purchase of goods and services using a cash register. Additionally,temporary seizure of movable property was added to the National Tax Administration Act. It consistsin the ability to seize the movable property of a taxpayer who is in arrears with payments to thetax authorities. This is done for a period of 96 hours. The enforcement authority may confirm theseizure or waive it. There are no direct provisions in the Polish Deal that would regulate tax audits.Several new approaches to the audit can be proposed in this regard. We may add to the regulationsa request for a tax audit at the demand of the auditee, or provisions permitting an audited entity torequest a selected audit activity, or a proposal to limit duration or number of audits at a taxpayers.The author proposes that one audit may be conducted once every five years at a given entity. A goodsolution in the first years of the Polish Deal may also be to apply lower penalties for mistakes in interpretingits provisions.
Keywords: tax audit; Polish Deal; verification purchase; temporary seizure of movable property